KAJIAN KEBUTUHAN ENERGI SPESIFIK DAN KAPASITAS KERJA MESIN PENGERING GABAH BERBAHAN BAKAR KAYU (Studi Kasus di Kelompok Tani Wargi Mekar, Desa Tegal, Kecamatan Karawang Timur, Kabupaten Karawang, Provinsi Jawa Barat) - Wahyu Kristian Sugandi; Boy Macklin P; Ahmad Thoriq; Fikrialdis Rifki (The University of Lampung, 2021)
Grain (Oryza sativa L) drying process is generally still done traditionally by direct sunlight. The drying process has several disadvantages such as it can only be done when sunlight is available, a longer drying time, a large area, requirement. An alternative that could be done to dry the grain in addition to using traditional drying was to use a grain dryer machines with do Wargi Mekar Farmer at Kerawang. There are several fuels that are used as heat sources for rice drying machines, one of them is firewood. This study aimed to measure the actual capacity of the wood-fired grain dryer, and also to analyzed the efficiency of drying and specific energy consumption to dry the grain. The research method used is descriptive analysis research method, namely data collection, data processing and data analysis. Research resulted that grain drying using a grain dryer as much as 761 kg.hr-1 . The yield of dry grain is 89.77%, and the value of weight loss is 10.33%. The moisture content of the material after drying is 13.06% wet basis. The drying efficiency in the process was 17.19% and the specific energy consumption was 15,318.24 KJ / Kg water vapor. Keywords: efficiency energy, grain drying, specific energy consumption